Formulation of a Manufacturing Strategy Using the House of Quality - Oddershede-Herrera, A; Palominos-Belmar, P; Quezada-Llanca, L (Elsevier B.V., 2019)
This paper describes a framework to formulate a manufacturing strategy based on the House of Quality (HOQ). This method consists of two main phases. The phase I relates what the market wants (the WHATs) with the manufacturing decision categories (the HOWs). The WHATs are expressed as the manufacturing objectives (i.e. cost, quality, delivery, flexibility and innovation) and the HOWs are expressed as the strategic manufacturing decisions areas (such as, facilities, capacity, process technology, new product design and control systems). A matrix is built, where the rows are the WHATs and the columns are the HOWs. The entries of the matrix are the relationships between both types of concepts. The “roof” of the house is the relationships between the manufacturing decisions (the HOWS). The analysis of this House allows managers to generate strategic action plans in order to fill the gap between what the market wants and what manufacturing is achieving. The phase II builds another house, where the WHATs are the manufacturing decision areas and the HOWS are strategic manufacturing plans. In this phase the strategic action plans are ranked. The application of the proposed method in a company that manufactures industrial tanks is shown. © 2019 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license (https://creativecommons.org/licenses/by-nc-nd/4.0/)